The Arts and Crafts of Syria and Egypt from the Ayyubids to World War I. Collected Essays, by Marcus Milwright - Vezzoli, Valentina (Journal of Islamic Archaeology, 2020)
The Arts and Crafts of Syria and Egypt from the Ayyubids to World War I. Collected Essays, by Marcus Milwright. Piscataway, NJ: Gorgia Press, 2018, 379pp., 97.20. ISBN-13: 9781463239008